2003
DOI: 10.1161/01.cir.0000052627.99976.18
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of C-Reactive Protein and Interleukin-6 in Patients With Obstructive Sleep Apnea Syndrome Are Decreased by Nasal Continuous Positive Airway Pressure

Abstract: Background-C-reactive protein (CRP) and interleukin (IL)-6 are important risk factors for atherosclerosis and coronary heart disease. In the present study, we examined serum levels of CRP and IL-6, IL-6 production by monocytes, and the effect of nasal continuous positive airway pressure (nCPAP) in patients with obstructive sleep apnea syndrome (OSAS). Methods and Results-After polysomnography, venous blood was collected at 5 AM from 30 patients with OSAS and 14 obese control subjects. Serum levels of CRP and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
586
8
47

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 883 publications
(662 citation statements)
references
References 40 publications
21
586
8
47
Order By: Relevance
“…Identification of these plaques with increased frequency on MDCT scans in patients with OSA is especially relevant, as prevalence of OSA is high in patients with ACS. 24 We also found that patients with OSA have significantly higher severity of stenosis and have significantly greater number of vessels involved as compared with the non-OSA group (P < 0.05).…”
Section: Discussionsupporting
confidence: 58%
“…Identification of these plaques with increased frequency on MDCT scans in patients with OSA is especially relevant, as prevalence of OSA is high in patients with ACS. 24 We also found that patients with OSA have significantly higher severity of stenosis and have significantly greater number of vessels involved as compared with the non-OSA group (P < 0.05).…”
Section: Discussionsupporting
confidence: 58%
“…72 Various studies have also found that C-reactive protein, tumor necrosis factor-a, interleukin-6 (IL-6), IL-8 and cell adhesion molecules such as intercellular adhesion molecule-1 are increased in the circulation in OSA patients independent of obesity. 10,15,73,74 Increased inflammation may have a role in the pathogenesis of OSA, increasing arterial stiffness and contributing to the early atherosclerosis found in OSA patients. 3 Furthermore, it also appears that endothelial dysfunction in OSA is partially mediated through apoptotic dysregulation; circulating apoptotic endothelial cells were found to be associated with AHI (r¼0.56, P¼0.004).…”
Section: Mechanismsmentioning
confidence: 99%
“…8 Although OSA patients commonly demonstrate one or more established cardiovascular risk factors, there is now a considerable body of evidence indicating that OSA itself is an independent cardiovascular risk factor. 3,[9][10][11][12][13][14][15][16] Arterial stiffness determines how quickly the pulse wave generated by the contracting heart travels to the periphery and is reflected back. The larger arteries of the cardiovascular system are critical in the conduction of blood flow to the periphery.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Atherosclerosis is a progressive disease that is also a pivotal risk factor for these cardiovascular disorders. OSA induces systemic HT, inflammation, 3 endothelial dysfunction 4 and disturbances in sympathetic activity, 5 all of which are known to accelerate the development of atherosclerosis. It has been shown that continuous positive airway pressure (CPAP) treatment improves these risk factors for atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%